Solving Maxwell's Equation in Meta-Materials by a CG-DG Method. (17th May 2016) - Xie, Ziqing; Wang, Jiangxing; Wang, Bo; Chen, Chuanmiao
Abstract: In this paper, an approach combining the DG method in space with CG method in time (CG-DG method) is developed to solve time-dependent Maxwell's equations when meta-materials are involved. Both the unconditional L 2 -stability and error estimate of order are obtained when polynomials of degree at most r is used for the temporal discretization and at most k for the spatial discretization. Numerical results in 3D are given to validate the theoretical results.